Hemorrhagic Retinal Detachment Following Severe Dengue Fever - A Case Report - Abhishek Varshney; Manmath Das (Delhi Journal of Ophthalmology)
A child suffering from dengue haemorrhagic fever, diagnosed elsewhere, reported to our hospital with complaints of sudden painless loss of vision in both eyes for 2 days. Ocular examination revealed profound visual impairment in both eyes, quiet anterior segment, vitreous haemorrhage and retinal detachment. Ultrasonography revealed haemorrhagic retinal detachment in both the eyes. Blood counts showed severe anaemia with thrombocytopenia. Considering the urgency of the systemic condition, he was referred to a multi-speciality hospital and was asked to review at the hospital when systemic parameters become stable. He did not return for follow up and expired a few months later.